2017
DOI: 10.18388/abp.2016_1340
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering soybean molecular stress response via high-throughput approach

Abstract: As a result of thousands of years of agriculture, humans had created many crop varieties that became the basis of our daily diet, animal feed and also carry industrial application. Soybean is one of the most important crops worldwide and because of its high economic value the demand for soybean products is constantly growing. In Europe, due to unfavorable climate conditions, soybean cultivation is restricted and we are forced to rely on imported plant material. The development of agriculture requires continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 93 publications
(132 reference statements)
0
14
0
Order By: Relevance
“…All five chilling-responsive miRNAs tested in this research (miR159, miR169, miR319, miR397, and miR398) are highly conserved in plants and have been associated with cold and other types of stress responses (Sunkar et al, 2012;Tyczewska et al, 2016). As reported in the literature, depending on the plant species, the expression patterns of these miRNAs differed in response to chilling stress.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…All five chilling-responsive miRNAs tested in this research (miR159, miR169, miR319, miR397, and miR398) are highly conserved in plants and have been associated with cold and other types of stress responses (Sunkar et al, 2012;Tyczewska et al, 2016). As reported in the literature, depending on the plant species, the expression patterns of these miRNAs differed in response to chilling stress.…”
Section: Discussionmentioning
confidence: 57%
“…Thus far, a number of groups have shown that miRNAs play a role in the response of soya bean to abiotic and biotic stressors (reviewed in Tyczewska, Gracz, Kuczyński, & Twardowski, 2016), such as heavy metals (Qiao-Ying et al, 2012), drought, salinity, alkalinity (Liu et al, 2016), phosphate starvation (Xu et al, 2013), and Phytophthora sojae (Wong et al, 2014) and cyst nematode infection (Li et al, 2012). In vegetable soya bean (Xu et al, 2016) and in nodules of G. max (Zhang, Wang, et al, 2014), the expression of several miRNAs has been identified to be significantly changed during chilling stress.…”
mentioning
confidence: 99%
“…miRNAs bind to complementary mRNA molecules and act as negative regulators of gene expression through endonucleolytic cleavage or translational repression of the cognate mRNA targets (Voinnet 2009). Lately, miRNA regulation of stress response pathway has been established in several plant species (Karimi et al 2016;Shu et al 2016;Song et al 2017;Tyczewska et al 2016). Consistently, a large number of cold stress responsive microRNAs have been identified in various plant species with variable results in different reports (Bej and Basak 2014;Megha et al 2017;Song et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Humans have domesticated and enhanced many crop types over thousands of years of agricultural growth, making them the basis of our daily diet, animal feed, and industrial applications [ 1 ]. Soybeans [ Glycine max (Linn.)…”
Section: Introductionmentioning
confidence: 99%